Palladium‐Catalyzed Direct Oxidative Esterification of Indoles at the C3 Position: A Novel Prospect for C(sp2)−H Acyloxylation. Issue 2 (15th January 2018) - Song, Jian; Cui, Jie; Liang, Hanbing; Liu, Qing; Dong, Yunhui; Liu, Hui
Abstract: An efficient palladium‐catalyzed direct oxidative esterification reaction of indoles with both aliphatic and aromatic carboxylic acids is reported. The use of Ag2 CO3 is crucial to this transformation, as it functions as both a base and an oxidant for the regeneration of the palladium(II) catalyst. This methodology represents a novel prospect for C(sp 2 )−H acyloxylation and will promote interest in direct C(sp 2 )−H esterification. Abstract : Double act : A novel methodology for C(sp 2 )−H acyloxylation is presented. Indoles efficiently underwent palladium‐catalyzed direct oxidative esterification with aromatic and aliphatic carboxylic acids. Ag2 CO3 acts as both a base and an oxidant for the regeneration of the palladium(II) catalyst.